Efemérides – Memoria nacional en la nomenclatura de Asunción (1942-2007) - Roberto L. Céspedes (Caravelle)
This paper, based upon historical sociology, deals with the building of a national memory through the ephemeris established in the Asunción nomenclature during recent history (1942-2007), and achieved via three historical steps (military nationalism-Stroessner Era-transition). This dates contribute to complete the construction of the official national memory. Nation is remembered through thirty-one street names : seventeen refer to war events, six to religious ones, five to events dealing with foundations or “births” and three represent civic nature.